Where has all the Youth Crime Gone? Youth Justice in an Age of Austerity. (September 2014) - Bateman, Tim
<x xml:space="preserve">Abstract</x> Youth justice under the Coalition government in England and Wales has been characterised by considerable gains — falling youth crime, increased diversion and substantial reductions in child imprisonment — that would generally be associated with a progressive agenda. Focusing on youth justice policy in England and Wales, this article suggests that the tensions implicit in a government of the new right delivering outcomes that demonstrate an increased tolerance to children who offend can be explained by the logic of austerity. That same logic brings with it other policy measures that are potentially less compatible with children's well‐being.